The influence of temperature on the phase behavior of ionic liquid aqueous two-phase systems. Issue 6 (3rd June 2019) - Li, Yuliang; Zhang, Nan; Xu, Shuai; Zhu, Qi; Hu, Jing
Abstract: In this article, the equilibrium behavior of solutions of 1-ethyl-3-methylimidazolium dimethyl phosphate ([Emim]DMP) and ethyl acetate or acetone in aqueous two-phase system (ATPS) was discussed to understand the liquid–liquid equilibrium (LLE) behavior of these organic solvents. Thus, we determined phase diagrams and LLE data at 303.15, 308.15, 313.15, and 323.15 K for the investigated biphasic systems. Four empirical equations were used to study the tie lines. The results showed that for the [Emim]DMP + acetone + water biphasic systems within the investigated temperature range, temperature influences the phase behavior, but for the [Emim]DMP + ethyl acetate + water biphasic systems within the investigated temperature range, there are no notable changes on the phase behavior with rising temperature. The results may have important applications for the separation of antibiotics and for the recovery of ionic liquids (ILs). Graphical Abstract: